Peran Guru Bahasa Indonesia Sebagai Role Model dalam Menumbuhkan Kehidupan Spiritual Siswa di SMP Negeri 7 Medan - Gabriella Br Kembaren; Frischa Saria S; Daniela Maretty Situmorang; Jesika Melissa Wati Simanjuntak; Melany Yohana Aprilya Manalu (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research aims to reveal the role of Indonesian language teachers as role models in cultivating students' spiritual lives. Through a qualitative approach, this research found that Indonesian language teachers have a significant influence in shaping students' character and spiritual values. Teachers are not only teachers, but also role models who inspire students to develop their spiritual potential. The research results show that teachers who are exemplary in implementing religious and moral values, and are able to create a conducive learning atmosphere, can trigger the growth of spiritual awareness in students.